Different meanings for cummingtonite-hornblende association in plutonic rocks (Iberian Massif, Portugal) - Solá, A. R. (2010)
Cummingtonite-grunerite series is frequently related with metamorphism or volcanic environments but rarely described as belonging to a plutonic assemblage [1]. Recently, in Iberian Massif (Portugal), there have been several references [2,3,4,5] of this Fe-Mg amphibole intimately associated with Ca amphiboles (mainly hornblende) on plutonic rocks. Different textural relations between two amphibole types have been argued to for a primary (igneous) or subsolidus metamorphic origin for Fe-Mg amphibole. Cummingtonite-grunerite (Cum, hereafter all abbreviation from [6]) from gabbros and diorites Carrascal Massif (Central Iberian Zone) occurs as tiny exsolution lamellae within a dominant hornblende (Hbl) crystal. Their textural occurrence agrees with the subsolidus growth of the Fe-Mg amphibole reflecting the equation Hbl+ Qtz= Cum + An + H2O [7]. Nevertheless, on Hospitais tonalite (Ossa-Morena Zone) Cum occur as euhedral to subhedral cores usually mantled by Hbl. Although seldom described in literature, Cum on Hospitais tonalite was interpreted as an igneous crystallizing early phase. As a consequence of the high water content of calc-alkaline magmas, the Fe-Mg amphibole should reflect the equation Opx+H2O = Cum+Mag+SiO2+H2 [8]. The similarity between Mg # on Cum and Hbl from tonalitic rocks suggests an equilibrium crystallizing assemblage as pointed by Wones and Gilbert [9] for a hypabyssal igneous suite. Considering that the Cum spectrum analyses from both occurrences exhibited a clear overlap; Carrascal gabbro-dorites (Mg#: 0.49-0.64; Al2O3: 0.7-2.37%; TiO2: 0.01-0.37%) and Hospitais tonalite (Mg#: 0.43-0.53; Al2O3: 1.22-2.44 %; TiO2; 0.05-0.27%), textural relations should be the main (only?) tool to decipher between igneous vs metamorphic growth. More detailed petrographic studies on plutonic rocks from Iberian Massif are needed to ascertain the petrogenetic significance of the association Cum-Hbl.